Znaczenie controllingu w zakładach opieki zdrowotnej - Kiełbasa, Monika (The Role of Controlling in Health Care Units, 2006)
The growing competition on market, changing legal conditions and economic activities of health care institutions coerced the introduction new - more effective methods of management. Just one of such methods is controlling. Although existence many definitions of the controlling it settles down usually to his basic function, what is bias towards achievement of established aims. In contradiction to control, controlling is oriented on future. Controlling realizes many functions e.g. counselling, supervision, coordination, methodical help, and also acts and counter-measures making. Well thoughtful and efficient working controlling is essential element of competitive superiority on market. It influences on enhancement of efficiency of acts and the same on increase value of company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1103, s. 181-191